(untitled) (Research, Society and Development, 2022)
Benznidazole (Bdz) are the drug of choice to treat Chagas Disease. However, the drug causes several side effects, and Trypanosoma cruzi, the etiological agent of Chagas disease, can be less susceptible to the action of drugs in the chronic phase, due to its reduced metabolism and dormancy in tissues. Thus, using compounds that are lethal to amastigote forms, which are prevalent in the Chagas disease chronic phase, is essential for the success of therapy. We propose to evaluate, though a systematic review, the efficacy of thiazolidine and its imidazolidine derivatives against T. cruzi intracellular amastigotes, and to compare the results with those for Bdz, A systematic search was made on eight English Language Systematic Databases - Science Direct, Scopus, Pubmed, Google Scholar, LILACS, Scielo, Trip Database and Cochrane, to collect studies, without a time scale. IC50 values, cytotoxic effects (CC50), a selective index (SI), the mechanism of action of each compound and the length of treatment was included in this review to evaluate the effectiveness of each compound. The compound 2-Iminothiazolidin-4-one 18 was more effective than Bdz, as it affected intracellular amastigotes by making a structural modification in the parasite, and by inhibiting cruzain, being promising for the antichagasic therapy.